«Чужая речь мне будет оболочкой…». Рец. на кн.: «Корни, побеги плоды…Мандельштамовские дни в Варшаве» [“Chuzhaia rech´mne budet obolochkoi...”: Korni, pobegi, plody ... Mandelshtamovskie dni v Warszawe. A review article] - Sergei Shindin (Slavica Revalensia)
In his contribution to the second volume of Slavica Revalensia, Sergei Shindin reviews the proceedings of the Warsaw Mandel’shtam conference (September 18—22, 2011) published in 2013 by the Russian State University for the Humanities.